2020
DOI: 10.1080/09537325.2020.1787374
|View full text |Cite
|
Sign up to set email alerts
|

Business model innovation in SMEs: the role of boundaries in the digital era

Abstract: The digital era is radically changing our societies and how firms do business. Innovating the business model has become a fundamental capability to survive competition, particularly for small and medium-sized enterprises (SMEs). This study investigates the digital-era role of boundary management capabilities in the processes of Business Model Innovation (BMI) in SMEs.Structural Equation Modeling is adopted to analyze data from a survey of 250 Italian experts who possess direct research and consulting experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 51 publications
4
52
0
1
Order By: Relevance
“…"real-traditional world," Chen and Zhang, 2014;Hartmann et al, 2016;Tian, 2017). For example, digitization increasingly opens up opportunities for firms to conceive and create innovative business models in two-sided markets (Caputo et al, 2019;Rochet and Tirole, 2006;Garzella et al, 2020) with interconnections between two or more customers that might or might not make monetary payments (i.e. "users," see Baden-Fuller et al, 2018;Erevelles et al, 2016;Tiago and Ver ıssimo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…"real-traditional world," Chen and Zhang, 2014;Hartmann et al, 2016;Tian, 2017). For example, digitization increasingly opens up opportunities for firms to conceive and create innovative business models in two-sided markets (Caputo et al, 2019;Rochet and Tirole, 2006;Garzella et al, 2020) with interconnections between two or more customers that might or might not make monetary payments (i.e. "users," see Baden-Fuller et al, 2018;Erevelles et al, 2016;Tiago and Ver ıssimo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…joint ventures, in-licensing, out-licensing and cross-licensing (Gambardella and Panico, 2014;Lombardi, 2019), Abulrub and Lee's (2012) study shows that firms use only a few types of the 13 identified modes of open innovation, including joint research development, contract R&D, customer involvement and external networking. In implementing open innovation modes, firms change their activities and processes by transforming innovation management models and business models (Zhu et al, 2019;Garzella et al, 2020;Saebi and Foss, 2015;Abdulkader et al, 2020) and sharing knowledge with producers, providers, users, research centres, universities and other network actors (Lombardi et al, 2016;Cassiman and Valentini, 2016;West and Bogers, 2013;Secundo et al, 2019). The involvement of several external resources has become a focal issue in recognizing firm boundary resources and in governing firms through strategic boundary management (Giannopoulou et al, 2010;West et al, 2014;Fiorentino, 2016).…”
Section: Boundary Management In Open Innovationmentioning
confidence: 99%
“…is not easy to distinguish firms from the external environment, it is increasingly necessary to use the concept of boundaries and the "boundary zone" as central elements of network dynamics, digital innovation and sharing economy perspectives (Caputo et al, 2021;Garzella et al, 2020;Nambisan et al, 2017). The management of resources, knowledge and activities on firm boundaries is becoming a new paradigm for obtaining and sustaining a competitive advantage (Dyer and Singh, 1998;Garzella, 2000;Wagner, 2003;Gonzalez-Benito and Lannelongue, 2014).…”
Section: Rq2 Which Boundary Resources and Activities Foster The Management And Implementation Of Open Innovation?mentioning
confidence: 99%
“…The impact of modern technologies and successive developments on information exchange technology such as the Internet and creative technologies and their perceptions in the minds of workers in companies and limited by institutional arrangements and their general impact on organizations (Garzella et al, 2020;Manesh et al, 2020). The impact of digital transformation in digital marketing is related to organizational change, organizational culture, new ways in which society deals with information, and the contemporary requirements of government services.…”
Section: Implication For Digital Marketingmentioning
confidence: 99%
“…The era of digitization has arisen as a result of the rapid development of information technology capabilities, which have affected every aspect of society. To exploit the great benefits of digital transformation requires a rapid adaptation in line with social and economic changes and poses additional challenges in how companies conduct their business in this way (Garzella et al, 2020). According to Caputo et al (2019) and Manesh et al (2020), new business models are needed to produce and achieve a competitive advantage.…”
Section: Implication For Digital Marketingmentioning
confidence: 99%